Literature Study: Complex Compounds Of Zn (II) EDTA, Mn (II) Netilisophyldithiocarbamate, and Lutesium-177(177lu)-Di-N-Butyl Dithiocarbamate In Industry - Nasution, Rida Anastasia; Simatupang, Septania Oniza; Jahro, Iis Siti; Nurfajriani (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study is a literature review aimed at analyzing the synthesis, characterization, functions, and potential hazards of three types of complex compounds used in industry, namely Zn(II)-EDTA, Mn(II)-N-ethylisopropyldithiocarbamate, and Lutetium-177(177Lu)-Di-n-butyldithiocarbamate. The research method employed was library research, focusing on reviewing various relevant scientific sources from both national and international journals. The results show that Mn(II)-N-ethylisopropyldithiocarbamate functions as a lubricant additive that enhances viscosity and reduces friction at high temperatures; Zn(II)-EDTA acts as an effective anti-algae agent in industrial cooling water systems due to its strong chelating properties; and 177Lu-Di-n-butyldithiocarbamate serves as a radiotracer in industrial process monitoring owing to its high stability and radiochemical purity. Despite their many advantages, these compounds also pose potential toxic and environmental risks if not properly managed. Therefore, further research is recommended to develop more efficient and environmentally friendly synthesis methods and to ensure their application complies with industrial and radiation safety standards.